Correlation of cone beam CT-derived bone density parameters with primary implant stability assessed by peak insertion torque and periotest in the maxilla. Issue 3 (March 2019) - Hakim, Samer G.; Glanz, Julia; Ofer, Markus; Steller, Daniel; Sieg, Peter
Abstract: Purpose: Primary implant stability is crucial to osseointegration. The aim of this study was to assess correlation of preoperative radiologic parameters with intraoperatively obtained biomechanical tests in the maxilla. Materials and methods: A total of 259 implants were inserted in the maxilla of 99 patients. Cone-beam computed tomography (CBCT)-derived Hounsfield units (HU), voxel grey values and computed tomography mental index (CTMI) performed preoperatively were correlated with insertion torque and Periotest (obtained intraoperatively and 12 weeks later) to assess their prognostic value for primary implant stability. Results: Voxel grey values and insertion torque showed a low correlation ( r = 0.329, p = 1.055 × 10 − 7 ). Likewise, a low correlation was found between HU measured preoperatively and insertion torque as well as intraoperative Periotest values ( r = 0.297, p = 4 × 10 − 6 and r = − 0.234, p = 4.35 × 10 − 4, respectively). A moderate correlation could, however, be assessed between insertion torque and intraoperative as well as Periotest values 12 weeks later. ( r = −0.555, p = 1.022 × 10 − 20 and −0.465. p = 1.150 × 10 − 13 ). On contrast, a high correlation was observed between the voxel grey values of CBCT and related HU ( r = 0.710, p = 6.486 × 10 − 37 ) so that a conversion from grey values into HU could be suggested. According to regression analysis, an intraoperative negative Periotest value could be expected at an insertion torque of 40 N/cm upwards. Conclusion: CBCT-based bone density parameters correlate with each other and allow conversion of grey scales into HU preoperatively. Both insertion torque and Periotest showed a significant correlation which enables regression analysis to predict implant stability for related insertion torque. On contrast, for HU the distribution curves do not allow a reliable assignment into certain Periotest values.